2015
DOI: 10.1021/acs.inorgchem.5b00392
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of (U0.7Pu0.3)O2-x Mixed Oxides

Abstract: Uranium-plutonium mixed oxide containing 30% of plutonium is a candidate fuel for several fast neutron and accelerator driven reactor systems. In this work, a detailed structural investigation on sol-gel synthesized stoichiometric U0.7Pu0.3O2.00 and substoichiometric U0.7Pu0.3O2-x, using X-ray diffraction (XRD), oxygen 17 magic angle spinning nuclear magnetic resonance ((17)O MAS NMR) and X-ray absorption spectroscopy is described. As observed by XRD, the stoichiometric U0.7Pu0.3O2.00 is monophasic with a latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…once plotted, the reticular parameter of the phase constituting the intermediate compositions Pu 1Ày Am y O 2.00 follows a line between the two pure poles. This trend is well known in stoichiometric uraniumplutonium mixed oxides (Truphé mus et al, 2013;Vauchy et al, 2014;Vigier et al, 2015;Elorrieta et al, 2017) but, to our knowledge, has never been clearly reported in the literature for plutonium-americium mixed oxides. The experimental lattice parameters are compared in Table 5 with literature data on Pu 1Ày Am y O 2 mixed oxides with similar americium contents y.…”
Section: Lattice Parameters At Room Temperaturesupporting
confidence: 58%
“…once plotted, the reticular parameter of the phase constituting the intermediate compositions Pu 1Ày Am y O 2.00 follows a line between the two pure poles. This trend is well known in stoichiometric uraniumplutonium mixed oxides (Truphé mus et al, 2013;Vauchy et al, 2014;Vigier et al, 2015;Elorrieta et al, 2017) but, to our knowledge, has never been clearly reported in the literature for plutonium-americium mixed oxides. The experimental lattice parameters are compared in Table 5 with literature data on Pu 1Ày Am y O 2 mixed oxides with similar americium contents y.…”
Section: Lattice Parameters At Room Temperaturesupporting
confidence: 58%
“…This is a crucial point to understand for the safety assessment of nuclear fuels because their thermal properties, as for instance the melting point and the thermal conductivity, which determine their behaviour in reactors and safety margins, are dramatically affected by changes in the O/M ratio. For this reason, the atomicscale properties of key U 1−y M y O 2±x solid solutions have been recently investigated using spectroscopic techniques such as XAS [2][3][4][5][6][7][8][9][10] , NMR 6 and Raman spectroscopy 7,[11][12][13] . For oxygenstoichiometric (O/M = 2.00) compounds such as (U,Ce)O 2 2 , (U, Th)O 2 14 , (U,Pu)O 2 3,8 and (U,Np)O 2 6 , each cation is in the tetravalent state and no oxygen vacancies nor interstitials are observed.…”
mentioning
confidence: 99%
“…The only effect generally observed on the local structure of these mixed dioxides is a variation of the metal-oxygen distance, consistent with the differences in the M 4+ ionic radii. Non-stoichiometric FCC (U,Pu)O 2±x oxides were also studied: for O/M<2, Pu 3+ , Pu 4+ and U 4+ coexist and oxygen vacancies are observed; 8 for O/M > 2, the presence of oxygen interstitials is balanced by a partial oxidation of uranium to U 5+ , whereas plutonium remains tetravalent 3 .…”
mentioning
confidence: 99%
“…Metal precipitates containing Pd, Ru, Rh but no Mo or Tc were scattered throughout the matrix. Diffraction Electron Precession (DEP) data have been collected in both regions and analyzed assuming a cubic Fm3 ̅ m structure of MOX [16]. In region 2 of Figure 19a, the proximity to the TEM grid attachment with possible local bending of the lamella made the data refinement uncertain, with a very low confidence index and poor image quality.…”
Section: Csmentioning
confidence: 99%